IMPLEMENTASI ASPEK MANAJEMEN BERBASIS SEKOLAH DALAM PELAYANAN BIMBINGAN DAN KONSELING - Diaty, Rima; Arisa, Azura; Ari Lestari, Nur Cahyani; Ngalimun, Ngalimun (Universitas Palangka Raya, 2022)
This study discusses the implementation of aspects of school-based management in counseling guidance services that occur in schools. The results are: school-based management in counseling guidance services is a management model that provides wider autonomy to schools including madrasas to manage school resources and encourage schools to increase the participation of school members and the community to achieve school goals within the framework of national education. The implementation of school-based management in counseling guidance in schools requires the cooperation and participation of school stakeholders. Such stakeholder groups are principals and their representatives, teachers, students, counselors, government representatives and representatives of educational organizations. Thus, the preparation of the BK program in schools requires the cooperation and participation of stakeholders and the preparation of the BK program in its implementation also requires openness.